Sub-wavelength annular-slit-assisted superoscillatory lens for longitudinally-polarized super-resolution focusing - Kim, Hyuntai (Sci Rep, 2020)
A binary metallic superoscillatory lens assisted with annular subwavelength slits is proposed, which generates a longitudinally-polarized super-resolution focal point. The annular slits are designed to selectively transmit radially-polarized light. Simulations using the finite element method show a 0.24 λ focal spot with 21.8 dB of polarization purity and only 0.342 dB reduction in efficiency compared to a standard superoscillatory lens.